The effect of medicarpin on PTEN/AKT signal pathway in head and neck squamous cell carcinoma - Yiğin, Aysel Kalayci; Donmez, Huseyin; Hitit, Mustafa; Seven, Sena; Eser, Nadire; Kurar, Ercan; Seven, Mehmet (Ovid Technologies (Wolters Kluwer Health), 2022)
Background/Aim: We aimed to investigate the in vitro modulating effects of medicarpin on the PI3K/AKT signal pathway gene expressions in head and neck squamous cell carcinoma (HNSCC). Materials and Methods: The effect of medicarpin on PTEN and other associated genes in the PTEN/AKT signal pathway was investigated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, real-time quantitative polymerase chain reaction, and Western blot analysis in the SCCL-MT1 (HNSCC) and control (HEK-293) cell lines. Results: The IC50 dose was 80 μM as a result of medicarpin treatment on HNSCC cells (P = 0.0006). It was found that PTEN and AKT gene expressions increased after the medicarpin administration while PDK1 gene expression was decreased in SCCL-MT1 cells (P = 0.0002, P = 0.0003, and P = 0.05, respectively). Protein expression results showed that medicarpin-treated cells significantly increased in pAKT (P = 0.024), pPTEN (P = 0.032), and decreased pPDK1 (P = 0.059) in SCCL-MT1. Conclusions: Our data show that medicarpin modulates HNSCC cells by increasing the PTEN and decreasing PDK1 expressions. PDK1 gene expression effects mTOR pathway which may increase AKT gene. Our study suggests that both medicarpin extracts combination with the HNSCC drug may be more effective in cancer treatment. Future prospective studies that integrate molecular and pharmacogenetic studies are crucial for revealing the mechanism and preventive medical efforts.
Keywords: Pterocarpans; Squamous Cell Carcinoma of Head and Neck; medicarpin; PTEN Phosphohydrolase; Head and neck squamous cell carcinoma; in vitro; Apoptosis; Sativa; Phosphatidylinositol 3-Kinases; PTEN/AKT signal pathway; HEK293 Cells; Head and Neck Neoplasms; Cell Line, Tumor; Humans; Prospective Studies; Proto-Oncogene Proteins c-akt; Cell Proliferation; Signal Transduction; 3. Good health